Kindergartens Reopening in the Period of Regular Epidemic Prevention and Control, Benefitial or Harmful? - Dong, Qiao-qiao (Curr Med Sci, 2020)
In the period of regular epidemic prevention and control of Coronavirus disease 2019 (COVID-19) in our country, work resumption has been fully advanced. But there are still new sporadic local cases and imported cases across the country. In this situation, whether kindergartens reopening will increase the risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spread still remains uncertain. We reviewed two pediatric patients with moderate COVID-19, collected the epidemiologic information and monitored the cycle threshold value of rectal specimen and the viral loads, and discussed the transmission of SARS-CoV-2 in pediatric patients and the virulence of feces in children with moderate COVID-19, in order to analyze the risk of kindergartens reopening.